2016
DOI: 10.1177/2047487316676133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mediterranean diet on endothelial progenitor cells and carotid intima-media thickness in type 2 diabetes: Follow-up of a randomized trial

Abstract: We assessed the long-term effects of a Mediterranean diet on circulating levels of endothelial progenitor cells (EPCs) and the carotid intima-media thickness (CIMT) in patients with type 2 diabetes. Design: This was a parallel, two-arm, single-centre trial. Methods: Two hundred and fifteen men and women with newly diagnosed type 2 diabetes were randomized to a Mediterranean diet (n ¼ 108) or a low-fat diet (n ¼ 107). The primary outcome measures were changes in the EPC count and the CIMT of the common carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 29 publications
1
73
0
1
Order By: Relevance
“…As recommended by the ADA guidelines, we found that the Mediterranean eating pattern has demonstrated effectiveness in improving glycaemic control as well as CVD risk factors and even in reducing CVD events . This diet appears to be appropriately considered helpful for T2D management; its inclusion in the recommended eating patterns is warranted.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…As recommended by the ADA guidelines, we found that the Mediterranean eating pattern has demonstrated effectiveness in improving glycaemic control as well as CVD risk factors and even in reducing CVD events . This diet appears to be appropriately considered helpful for T2D management; its inclusion in the recommended eating patterns is warranted.…”
Section: Resultsmentioning
confidence: 77%
“…Among the included trials are several large‐scale studies, one with 3614 participants and one with more than 200 participants . Longer‐term studies include one lasting 12 months, one lasting 24 months, and two lasting longer than 4 years …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent meta-analyses of RCTs have shown that when comparing with a variety of control diets, a Mediterranean style diet has beneficial effects on glycemic control, weight loss and cardiovascular risk factors among individuals with T2DM [160,161]. Furthermore, recent results from the long term MÉDITA trial showed that when compared with a standard low-fat diet, a Mediterranean diet ameliorates the inflammatory response and improves endothelial functioning in persons with T2DM [162,163]. Therefore, the efficacy of a MedDiet pattern in a cohort of older adults whom are vulnerable to an accelerated decline in SMM and function warrants future investigation.…”
Section: Implications For Future Research and Conclusionmentioning
confidence: 99%